Tumor promoting capacity of polymorphonuclear myeloid-derived suppressor cells and their neutralization - Groth, Christopher; Bitsch, Rebekka; Lasser, Samantha; Özbay Kurt, Feyza Gül; Kurzay, Annina; Petrova, Vera; Altevogt, Peter; Utikal, Jochen; Umansky, Viktor (International journal of cancer, 2021)
Myeloid-derived suppressor cells (MDSC) represent a highly immunosuppressive population that expands in tumor bearing hosts and inhibits both T and NK cell antitumor effector functions. Among MDSC subpopulations, the polymorphonuclear (PMN) one is gaining increasing interest since it is a predominant MDSC subset in most cancer entities and inherits unique properties to facilitate metastatic spread. In addition, further improvement in distinguishing PMN-MDSC from neutrophils has contributed to the design of novel therapeutic approaches. In this review, we summarize the current view on the origin of PMN-MDSC and their relation to classical neutrophils. Furthermore, we outline the metastasis promoting features of these cells and promising strategies of their targeting to improve the efficacy of cancer immunotherapy.
Gesehen am 30.03.2023